Iron(III)-Catalyzed Nucleophilic Substitution of the Hydroxy Group in Benzoin by Alcohols - Mirzaei, Anvar; Biswas, Srijit; Samec, Joseph S. M. (Synthesis, 2012)
The etherification reaction between benzoin derivatives and alcohols catalyzed by iron(III) proceeds in moderate to good yields. Other metal complexes showed either low reactivity or low chemoselectivity where oxidation of benzoin to benzil was a competing reaction. The iron source operated as a catalyst where 5 mol% of iron(III) generate the 2-alkoxy-1,2-diphenylethan-1-one in 50% yield. With an optimum of 25 mol% of catalyst, the desired ether was obtained in 85% yield. The etherification of benzoin and an alcohol proceed to generate the desired product in polar solvents such as 1,2-dichloroethane, whereas less polar solvents promote the competing oxidation to generate the benzil; polar coordinating solvents such as tetrahydrofuran inhibited the reaction. The efficiency of the reaction is found to be dependent on nucleophile where an optimum of 30 equivalents of alcohol was observed. With electron-donating substituents on the aromatic ring, the etherification was followed by oxidation to generate the benzil. Moderate yields of etherification product were obtained by monitoring the reaction progress with electron-rich substrates and quenching the reaction after two hours.
Keywords: iron catalysis; Lewis acids; substitution; ethers; alcohols